Nanochitin and Nanochitosan in Pharmaceutical Applications: Innovations, Applications, and Future Perspective - José Roberto Vega-Baudrit; Mary Lopretti; Gabriela Montes de Oca; Melissa Camacho; Diego Batista; Yendry Corrales; Andrea Araya; Badr Bahloul; Yohann Corvis; Luis Castillo-Henríquez (Pharmaceutics)
Nanochitin is a nanoscale form of chitin—a polysaccharide found in the exoskeletons of crustaceans, insects, and some fungal cell walls—that is newly garnering significant attention in the pharmaceutical space. Its good properties, such as biocompatibility, biodegradability, and an easily adjustable surface, render it attractive for various medical and pharmaceutical applications. Nanochitin, from drug delivery systems and wound-care formulations to vaccine adjuvants and antimicrobial strategies, has demonstrated its strong potential in meeting diverse therapeutic needs. This review covers the background of nanochitin, including methods for its extraction and refining and its principal physicochemical and biological properties. It further discusses various hydrolysis and enzymatic approaches for the structural and functional characterization of nanochitin and highlights some pharmaceutical applications where this biopolymer has been studied. The review also addresses toxicity issues, regulatory matters, and challenges in large-scale industrial production. Finally, it underscores novel avenues of investigation and future opportunities, emphasizing the urgent requirement for standardized production methods, rigorous safety assessment, and interdisciplinary partnerships to maximize nanochitin’s potential in pharmaceutical research, demonstrating the importance of chitin in drug delivery.